ANALISIS FAKTOR RISIKO KEJADIAN STUNTING PADA BALITA USIA 6 BULAN – 23 BULAN DI PUSKESMAS PEKKAE KECAMATAN TANETE RILAU KABUPATEN BARRU TAHUN 2020 - Nur Alda Fadillah; Andi Alifia Ayu Delima; Rauly Rahmadhani; Nadyah Haruna; Ibrahim Manda (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2022)
Stunting is ashort body condition according to the age which exceed the 2 SD (Standard Deviation) deficit below the median length standard or the height of the age. A toddler with stunting shows the existence of long-term nutritional problems or chronic nutrition that can be affected by the condition of the mother or future mother, fetal period and infancy or toddler period, including the disease suffered during infancy period. The aim of this research was to find out the risk factor of stunting to the child aged 6-23 months in working area of Pekkae health care, Tanete Rilau, Barru Regency. This research was a quantitative research with observational analytic method and crossectional design. Sampling was obtained by using purposive sampling technique. The total of sample were 98 toddlers and their mother as a respondent. The data were analyzed by using the Chi-square p0.05 in the SPSS program. The result of this research showed that there was a significant relationship between the history of complementary feeding (p-value 0.031;1.36), infectious disease (p-value 0.005;1.41),  mother’s knowledge of toddler nutrition (p-value 0.031;1.36) and economic factor (p-value 0.000; 2,71) toward the stunting. There was no significant relationship between the history of exclusive breastfeeding, toddler immunization, maternal height and the mother’s last education level toward this stunting with p-value 0.005. The most dominant factor in this research was family economic factor.Keywords : toddler, stunting, history of complementary feeding, history of infectious disease, mother’s education, mother’s knowledge, family economic factor.